Mild and Rapid Light‐Driven Suzuki‐Miyaura Reactions Catalyzed by AuPd Nanoparticles in Water at Room Temperature. Issue 12 (1st December 2022) - Nazar de Souza, Ana Paula; de Souza Tomaso, Luiz Phelipe; S. da Silva, Vitor Alexandre; S. da Silva, Gabriel Francisco; Santos, Evelyn C. S.; de S. Baêta, Eustáquio; Brant de Campos, José; Carvalho, Nakédia M. F.; Malta, Luiz Fernando B.; Senra, Jaqueline D.
Abstract: Organic reactions carried out in water under mild conditions are state‐of‐the‐art in terms of environmentally benign chemical processes. In this direction, plasmonic catalysis can aid in accomplishing such tasks. In the present work, cyclodextrin‐mediated AuPd bimetallic nanoparticles (NPs) were applied in room‐temperature aqueous Suzuki‐Miyaura reactions aiming at preparing biaryl products based on fluorene, isatin, benzimidazole and resorcinol, with yields of 77 % up to 95 %. AuPd NPs were revealed to be a physical mixture of Au and Pd particles circa 20 and 2 nm, respectively, through X‐ray diffraction, dynamic light scattering, UV‐Vis spectroscopy and transmission electron microscopy analyses. Abstract : In a bimetallic catalytic system, Au nanoparticles of ∼20 nm function as an antenna that harvests light energy and can improve the activity of cyclodextrin‐stabilized palladium nanoparticles (c∼2 nm) for room‐temperature aqueous Suzuki‐Miyaura reaction producing organic structural cores for biological and electrooptical applications.